2000
DOI: 10.1038/35001088
|View full text |Cite
|
Sign up to set email alerts
|

The genome sequence of the food-borne pathogen Campylobacter jejuni reveals hypervariable sequences

Abstract: Campylobacter jejuni, from the delta-epsilon group of proteobacteria, is a microaerophilic, Gram-negative, flagellate, spiral bacterium-properties it shares with the related gastric pathogen Helicobacter pylori. It is the leading cause of bacterial food-borne diarrhoeal disease throughout the world. In addition, infection with C. jejuni is the most frequent antecedent to a form of neuromuscular paralysis known as Guillain-Barré syndrome. Here we report the genome sequence of C. jejuni NCTC11168. C. jejuni has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

53
2,174
4
19

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,814 publications
(2,265 citation statements)
references
References 30 publications
53
2,174
4
19
Order By: Relevance
“…17 Among them, we found that some microorganisms belonging to the epsilon and delta categories in Proteobacteria, such as H. pylori, Wolinella succinogenes, C. jejuni and Geobacter sulfurreducens, a part of actinobacteria, such as S. coelicolor and S. avermitilis, and certain Deinococcus-Thermus bacteria, such as Thermus thermophilus and Deinococcus radioduran and so on, had no men gene orthologs despite the fact that these strains synthesize MKs. Among them, we selected four microorganisms, H. pylori, 13 C. jejuni, 14 T. thermophilus 18 and S. coelicolor, 11 as query microorganisms. With regard to subject microorganisms, in which the known MK biosynthetic pathway was operating, E. coli, 19 B. subtilis, 20 Corynebacterium glutamicum 21 and Mycobacterium tuberculosis 22 were selected.…”
Section: In Silico Screening For Candidate Genes Responsible For the mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Among them, we found that some microorganisms belonging to the epsilon and delta categories in Proteobacteria, such as H. pylori, Wolinella succinogenes, C. jejuni and Geobacter sulfurreducens, a part of actinobacteria, such as S. coelicolor and S. avermitilis, and certain Deinococcus-Thermus bacteria, such as Thermus thermophilus and Deinococcus radioduran and so on, had no men gene orthologs despite the fact that these strains synthesize MKs. Among them, we selected four microorganisms, H. pylori, 13 C. jejuni, 14 T. thermophilus 18 and S. coelicolor, 11 as query microorganisms. With regard to subject microorganisms, in which the known MK biosynthetic pathway was operating, E. coli, 19 B. subtilis, 20 Corynebacterium glutamicum 21 and Mycobacterium tuberculosis 22 were selected.…”
Section: In Silico Screening For Candidate Genes Responsible For the mentioning
confidence: 99%
“…11,12 Some pathogenic microorganisms, such as Helicobacter pylori 13 and Campylobacter jejuni, 14 which are known to cause gastric carcinoma and diarrhea, respectively, also lacked these five men gene orthologs, although they synthesize MK. 15,16 In contrast, these microorganisms possessed orthologs of menA and menG, 13,14 which catalyze a prenylation and a methylation, respectively, suggesting that the naphthoquinone moiety of MK would be synthesized through an alternative pathway.…”
Section: Introductionmentioning
confidence: 99%
“…For sequencing, PCR was performed with specific primers for amplification of QRDR in the gyrA gene, CjgyrA QRDR F and CjgyrA QRDR R (PARKHILL et al, 2000;PRICE et al, 2005). The Invitrogen kit (Life Technologies/USA) was used for the reaction, with 1X PCR Buffer (500mM KCl, 100mM Tris-HCl [pH 9.0]); 5μL (1mM each) dATP, dCTP, dGTP e dTTP; 0.5μL from each primer, 1.0U Taq DNA polymerase and 2mM MgCl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…C. jejuni is a commensal in many bird species, including poultry, and contaminated chicken meat is a major source of infection (Ketley, 1997). The genome sequence of C. jejuni strain NCTC 11168 was published in 2000 (Parkhill et al, 2000), and several other strains have been recently sequenced including strains 81116 (Pearson et al, 2007) and 81-176 (Hofreuter et al, 2006). Oxidative and nitrosative stresses are major factors that pathogens must combat in order to survive both outside and inside the host.…”
Section: Introductionmentioning
confidence: 99%